Environmental disclosure quality: examining the impact of the stock exchange of Malaysia's listing requirements - Fatima, A. H.; Abdullah, Norhayati; Sulaiman, Maliah (Emerald Group Publishing Limited, 2015)
The purpose of this study is to investigate the environmental disclosure (ED) quality of public-listed companies (PLCs) in environmentally sensitive industries (ESI) in Malaysia in 2005 and 2009 (two years before and two years after the mandatory corporate social responsibility (CSR) requirement of Bursa Malaysia (BM)). BM (The Stock Exchange of Malaysia) has made CSR, including ED in annual reports mandatory since 2007. This study compares environmental reporting (ER) before and after the 2007 mandatory reporting requirement to determine if this command and control mechanism has had any effect on the quality of ED. Design/methodology/approach - The quality of ED was measured using a disclosure quality index adapted from various prior studies. The index consists of a total of 46 disclosure items grouped into 9 categories. Content analysis was utilized to extract data from the annual reports of 164 PLCs in ESI. Findings - Overall, the quality of ED improved in 2009 from that of 2005. More importantly, companies disclosed more quantitative environmental information in 2009 than in 2005. However, the average quality of ED was still low in 2009 compared to the overall potential score. Results provide some support for legitimacy as well as institutional theories. Research limitations/implications - The sample of the study consisted of listed companies in ESI only; the results cannot be generalized to other companies in non-environmentally sensitive sectors. Practical implications - Prior studies that used data before the mandatory CSR requirement by BM found ED in annual reports mainly declarative in nature, generally low on quality and with little quantifiable data. The results of the present study provide evidence of the positive impact of mandatory environmental reporting on ED quality. Originality/value - The use of a multi-theoretical perspective may offer a more meaningful explanation of ER behavior in Malaysia. The results of the study would provide the impetus for regulatory agencies in developing countries to perhaps consider legislating ER. The findings provide some evidence to support the influence of legitimacy and institutional factors behind improved ED of Malaysian PLCs. This outcome exhibits a positive influence on the government efforts in promoting sustainability. Finally, the study contributes to present a more up-to-date account of environmental commitment undertaken by Malaysian corporations through their environmental reporting, after the CSR mandatory listing requirement took effect in 2007.